2015
DOI: 10.2217/pgs.14.167
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Pharmacogenomic-Guided Warfarin Treatment for Elderly Croatian Atrial Fibrillation Patients with Ischemic Stroke

Abstract: Overall, our data indicate that PGx-guided warfarin treatment may represent a cost-effective therapy option for the management of elderly patients with atrial fibrillation who developed ischemic stroke in Croatia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 42 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Total treatment cost per patient was lower for screening (€2772 [$3767]) than for non-screening (€2817 [$3828]).Improved safety, reduced cost[30]2015,2015, The Department of Neurology, University Hospital Center Zagreb, 206 patientsOf patients in the genotype-guided group ( CYP2C9, VKORC 1), 97% did not have any major complications compared with the control group.Estimated total cost per patient had a nonsignificant difference between genotype-guided and control group. However, the mean cost of bleeding was estimated to have significant difference at €119.32 (95% CI: €41.95–202.69) in favor of the PGx group.Improved safety, reduced cost[31]2015, AssureRx Health, Mayo Clinic, 258 patientsGene-guided treatment raised the odds of clinical response by 2.3-fold, the guided group had a 53% greater improvement in depressive symptoms.Improved efficacy[32]2015, College of Pharmacy, University of Utah, 1025 patientsPre-emptive screening with a panel-based approach resulted in a significant reduction in hospitalizations (9.8% vs 16.1%, P = 0.027) and patient visits to the emergency department (4.4% vs 15.4%, P = 0.0002).Reduced hospitalization, reduced cost[33]2015, Assurex Health, Mason, Prospectively generated cohort, Initially 2168 cases and 10,880 controlsPatients receiving PGx testing saved $1035.60 in total medication costs over 1 year compared to the usual care cohort ( P = 0.007). PGx testing improved adherence compared to standard of care.Reduced cost, improved adherence[34]2014, Vanderbilt University, PREDICT study, 10,000 patientsComparison of pre-emptive testing and reactive genotyping revealed that 14,656 tests would have been generated with point of care genotyping—the pre-emptive approach saves genotyping test costs by reducing the number of ordered tests by 60%.Reduced cost[21]2013, The EU-PACT trial, 455 patientsIn the genotype-guided group, the mean percentage of time in therapeutic range was 7.0 percentage points higher than in the control group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total treatment cost per patient was lower for screening (€2772 [$3767]) than for non-screening (€2817 [$3828]).Improved safety, reduced cost[30]2015,2015, The Department of Neurology, University Hospital Center Zagreb, 206 patientsOf patients in the genotype-guided group ( CYP2C9, VKORC 1), 97% did not have any major complications compared with the control group.Estimated total cost per patient had a nonsignificant difference between genotype-guided and control group. However, the mean cost of bleeding was estimated to have significant difference at €119.32 (95% CI: €41.95–202.69) in favor of the PGx group.Improved safety, reduced cost[31]2015, AssureRx Health, Mayo Clinic, 258 patientsGene-guided treatment raised the odds of clinical response by 2.3-fold, the guided group had a 53% greater improvement in depressive symptoms.Improved efficacy[32]2015, College of Pharmacy, University of Utah, 1025 patientsPre-emptive screening with a panel-based approach resulted in a significant reduction in hospitalizations (9.8% vs 16.1%, P = 0.027) and patient visits to the emergency department (4.4% vs 15.4%, P = 0.0002).Reduced hospitalization, reduced cost[33]2015, Assurex Health, Mason, Prospectively generated cohort, Initially 2168 cases and 10,880 controlsPatients receiving PGx testing saved $1035.60 in total medication costs over 1 year compared to the usual care cohort ( P = 0.007). PGx testing improved adherence compared to standard of care.Reduced cost, improved adherence[34]2014, Vanderbilt University, PREDICT study, 10,000 patientsComparison of pre-emptive testing and reactive genotyping revealed that 14,656 tests would have been generated with point of care genotyping—the pre-emptive approach saves genotyping test costs by reducing the number of ordered tests by 60%.Reduced cost[21]2013, The EU-PACT trial, 455 patientsIn the genotype-guided group, the mean percentage of time in therapeutic range was 7.0 percentage points higher than in the control group.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the Netherlands estimated that the total cost per patient was lower when screening, resulting in a cost savings of €45 ($61) per patient [30]. In warfarin treatment, the incremental cost-effectiveness ratio of PGx-guided therapy was estimated to be €31,225 per quality-adjusted life-years compared to the control group [31]. A study by AltheaDx, which aimed to survey the benefits of pharmacogenetics on the medical management of patients, found an estimated annual saving of €549 ($621) per patient that was tested [29].…”
Section: Introductionmentioning
confidence: 99%
“…Second, PGx can contribute toward reducing drug switches and recurrent drug dose adjustments, used until optimal clinical effect is achieved, and thereby reducing drug costs. Furthermore, PGx can also reduce the time until disease remission, therefore contracting hospitalization length, which positively impacts on the hospital treatment costs [60]. Last, PGx reduces disease burden and related costs, which includes loss of productivity, both in terms of absenteeism (absence from work) and presenteeism (be present at work but less productive) [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have aimed at assessing the costeffectiveness of genome-guided interventions in cardiology. In particular, Mitropoulou et al (2015) attempted prospectively to evaluate the cost-effectiveness of warfarin treatment in Croatian elderly ischemic stroke patients with atrial fibrillation. These authors have shown that pharmacogenomics-guided warfarin treatment represented a cost-effective therapeutic option for the management of these patients, with an estimated incremental cost-effectiveness ratio of the pharmacogenomicsguided versus the control groups of e31,225/QALY (Quality-Adjusted Life Year).…”
Section: Economics In Genomic Medicinementioning
confidence: 99%